(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The role of mother is a determinant factor for managing family food consumption. This study is aim to evaluate the relationship between the work status of mother and feeding practices pattern, food preparation pattern, and nutritional status of children aged 0-59 month. This study envolve 71 house wives who have children under five years lived in Nogotirto, Sleman residence, Yogyakarta. The 71 sample selected purposively with the criteria that the children lived in the same home with their mother, not sick and did not have a history of cronical diseases. The data on the energy and protein consumption were collected by using recall 24 hours method for 2 days inrespectively. Body weight measurement was done through weighing and respondent general information, feeding practices pattern and food preparation pattern were taken by interviewing using questionare. The result showed that almost all mother have a good score in feeding practices pattern (85,9%), food preparation pattern (81,69%). Consumption indicated that for energy was 56,34% and protein was 11,27%. Most children have a good nutritional status (83,1%). The relationship (p